Safety and activity of anti‐CD14 antibody IC14 (atibuclimab) in ALS: Experience with expanded access protocol. Issue 5 (30th December 2022) - Gelevski, Dario; Addy, Grace; Rohrer, Margot; Cohen, Caroline; Roderick, Aimee; Winter, Allison; Carey, Judith; Scalia, Jennifer; Yerton, Megan; Weber, Harli; Doyle, Michael; Parikh, Neil; et al.
Abstract: Introduction/Aims: IC14 (atibuclimab) is a monoclonal anti‐CD14 antibody. A previous phase 1 trial of 10 participants with amyotrophic lateral sclerosis (ALS) demonstrated initial safety of IC14 in an acute treatment setting. We provided long‐term treatment with IC14 to individuals with ALS via an expanded access protocol (EAP) and documented target engagement, biomarker, safety, and disease endpoints. Methods: Participants received intravenous IC14 every 2 weeks. Consistent with United States Food and Drug Administration guidelines, participants were not eligible for clinical trials and the EAP was inclusive of a broad population. Whole blood and serum were collected to determine monocyte CD14 receptor occupancy (RO), IC14 levels, and antidrug antibodies. Ex vivo T‐regulatory functional assays were performed in a subset of participants. Results: Seventeen participants received IC14 for up to 103 weeks (average, 30.1 weeks; range, 1 to 103 weeks). Treatment‐emergent adverse events (TEAEs) were uncommon, mild, and self‐limiting. There were 18 serious adverse events (SAEs), which were related to disease progression and unrelated or likely unrelated to IC14. Three participants died due to disease progression. Monocyte CD14 RO increased for all participants after IC14 infusion. One individual required more frequent dosing (every 10 days) to achieve over 80% RO. Antidrug antibodies were detected in only one participant and were transient, low titer, and non‐neutralizing. Discussion: Administration of IC14 in ALS was safe and well‐tolerated in this intermediate‐size EAP. Measuring RO guided dosing frequency. Additional placebo‐controlled trials are required to determine the efficacy of IC14 in ALS. Abstract : See Editorial on pages 337–338 in this issue .